Ischemic Stroke Occurs Less Frequently in Patients With COVID-19: A Multicenter Cross-Sectional Study. Issue 12 (December 2020) - Bekelis, Kimon; Missios, Symeon; Ahmad, Javaad; Labropoulos, Nicos; Schirmer, Clemens M.; Calnan, Daniel R.; Skinner, Jonathan; MacKenzie, Todd A.
Abstract : Background and Purpose: The impact of coronavirus disease 2019 (COVID-19) on the occurrence of ischemic stroke has been the subject of increased speculation but has not been confirmed in large observational studies. We investigated the association between COVID-19 and stroke. Methods: We performed a cross-sectional study involving patients discharged from a healthcare system in New York State, from January to April 2020. A mixed-effects logistic regression analysis and a propensity score–weighted analysis were used to control for confounders and investigate the association of COVID-19 with ischemic stroke. Similar techniques were used to detect the impact of concurrent COVID-19 infection on unfavorable outcomes for patients with stroke. Results: Among 24 808 discharges, 2513 (10.1%) were diagnosed with COVID-19, and 566 (0.2%) presented with acute ischemic stroke. Patients diagnosed with COVID-19 were at one-quarter the odds of stroke compared with other patients (odds ratio, 0.25 [95% CI, 0.16–0.40]). This association was consistent in all age groups. Our results were robust in sensitivity analyses, including propensity score–weighted regression models. In patients presenting with stroke, concurrent infection with severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) was associated with higher case-fatality (odds ratio, 10.50 [95% CI, 3.54–31.18]) and a trend towards increased occurrence of discharge to rehabilitation (odds ratio, 2.45 [95% CI, 0.81–1.25]). Conclusions: Using a comprehensive cross-section of patients from a large NY-based healthcare system, we did not identify a positive association between ischemic stroke and COVID-19. However, patients with stroke with COVID-19 had worse outcomes compared with those without, with over a 9-fold increase in mortality. Although no definitive conclusions can be reached from our observational study, our data do not support the concerns for an epidemic of stroke in young adults with COVID-19. Abstract : Supplemental Digital Content is available in the text.